2011
DOI: 10.1002/ejic.201100323
|View full text |Cite
|
Sign up to set email alerts
|

Consecutive C–F Bond Activation of Hexafluorobenzene and Decafluorobiphenyl

Abstract: The reaction of [Ni2(iPr2Im)4(COD)] (1) {iPr2Im = 1,3‐bis(isopropyl)imidazolin‐2‐ylidene} with hexafluorobenzene and decafluorobiphenyl results at room temperature in the formation of the products of a C–F bond activation reaction, i.e. [Ni(iPr2Im)2(F)(C6F5)] (2) and [Ni(iPr2Im)2(F)(C12F9)] (4). The reactions of 2 and 4 with 1 or the reactions of hexafluorobenzene and decafluorobiphenyl with 1 equiv. or excess of dinuclear 1 (stoichiometric ratio nickel/substrate > 2:1) at higher temperatures afford the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 35 publications
1
34
0
Order By: Relevance
“…Subsequent activations are disfavored due to the steric profile of the N‐heterocyclic ring. Radius and co‐workers reported the first example of a transition‐metal‐mediated double oxidative addition of C 6 F 6 , utilizing a bimetallic nickel‐NHC complex . Chemoselective C−H and subsequent regioselective C−F activation of C 6 F 5 H resulted in complex…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent activations are disfavored due to the steric profile of the N‐heterocyclic ring. Radius and co‐workers reported the first example of a transition‐metal‐mediated double oxidative addition of C 6 F 6 , utilizing a bimetallic nickel‐NHC complex . Chemoselective C−H and subsequent regioselective C−F activation of C 6 F 5 H resulted in complex…”
Section: Resultsmentioning
confidence: 99%
“…Radius and co-workersr eported the first example of at ransition-metal-mediated double oxidative addi-tion of C 6 F 6 ,u tilizing ab imetallic nickel-NHC complex. [33] Chemoselective CÀHa nd subsequent regioselective CÀFa ctivation of C 6 F 5 Hr esulted in complex 12.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past years we investigated the chemistry of the dinuclear, NHC‐stabilized nickel complex [Ni 2 ( i Pr 2 Im) 4 ( μ ‐( η 2 : η 2 )‐COD)] (NHC = N ‐heterocyclic carbene; i Pr 2 Im = 1,3‐di iso propyl‐imidazolin‐2‐ylidene; COD = 1,5‐cyclooctadiene) in stoichiometric and catalytic reactions in some detail. We reported the reactivity of this compound with respect to different molecules such as carbon monoxide, olefins, alkynes, silanes, nitriles, thioethers, sulfoxides, sulfones, and aryl halides, and especially with respect to organofluorides . We demonstrated that [Ni 2 ( i Pr 2 Im) 4 ( μ ‐( η 2 : η 2 )‐COD)] and related molecules are reasonable catalysts for different reactions such as the dehydrogenative coupling of silanes, the hydrogenation of selected polysilanes, the hydrodefluorination of polyfluoroaromatics, the borylation of aryl fluorides and aryl chlorides and for different cross coupling reactions .…”
Section: Introductionmentioning
confidence: 99%
“…We reported the reactivity of this compound with respect to different molecules such as carbon monoxide, olefins, alkynes, silanes, nitriles, thioethers, sulfoxides, sulfones, and aryl halides, and especially with respect to organofluorides . We demonstrated that [Ni 2 ( i Pr 2 Im) 4 ( μ ‐( η 2 : η 2 )‐COD)] and related molecules are reasonable catalysts for different reactions such as the dehydrogenative coupling of silanes, the hydrogenation of selected polysilanes, the hydrodefluorination of polyfluoroaromatics, the borylation of aryl fluorides and aryl chlorides and for different cross coupling reactions . In the course of our studies we became interested in the stability of different NHC‐ligated nickel(II) aryl and alkyl complexes of the type [Ni(NHC) 2 (R) 2 ] (R = alkyl, aryl) and [Ni(NHC) 2 (R)(X)][1j], [2h], [3f] and wanted to expand these investigations on bis(organyl) substituted nickel(II) complexes which are stabilized by only one N ‐alkyl‐substituted, comparably small NHC‐ligand.…”
Section: Introductionmentioning
confidence: 99%
“…[25] In the last few years NHCs have been explored mainly in 3d transition-metal chemistry, for instance in the dinuclear nickel complex [Ni 2 {ImA C H T U N G T R E N N U N G (iPr) 2 } 4 A C H T U N G T R E N N U N G (COD)] (COD = 1,5-cyclooctadiene) in stoichiometric element-element bond cleavage reactions and the application of these reactions in catalytic processes. [26][27][28][29][30][31][32][33][34] It was shown that this complex acts as a source for the [Ni{ImA C H T U N G T R E N N U N G (iPr) 2 } 2 ] complex fragment in C À F, C À C, C À S, S À S, and S À H bond activation reactions.…”
Section: Introductionmentioning
confidence: 99%